ANALISIS PELAYANAN LISTRIK PRABAYAR DI PT PLN (PERSERO) RAYON SEMARANG TENGAH (STUDI KASUS TENTANG PENANGANAN KELUHAN PELANGGAN LISTRIK PRABAYAR PT PLN (PERSERO) RAYON SEMARANG TENGAH - Yusi Ika Merlin; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2014)
The level of welfare and public services is directly proportional relationship. In connection with the assignment of  PT PLN to serve and provide public service,so PT PLN has the creation of a quality service. The focus of research is the Prepaid Electricity program, especially customer service complaint handling prepaid electricity. The purpose of the study was to describe services handling customer complaints "Prepaid Electricity" and knowing the dimensions of what is preventing customer complaints handling service "Prepaid Electricity" in PT PLN (Persero) Semarang Central Rayon. Good size bad service at PT PLN (Persero) Semarang Central Rayon uses four (4) dimensions of service delivery (service customer complaints). Four dimensions are empathy to angry customers, speed in handling complaints, liabilities or equity in solving a problem or complaint, it easy for customers to contact the company. This study used a descriptive qualitative type of customer respondents "Prepaid Electricity" PT PLN (Persero) Semarang Central Rayon encountered at the customer service counter or in the residence of the customer, the customer is doing an interactive telephone contact center with 123 PLN, Officer / Employee of PT PLN (Persero ) Semarang Central Rayon related to Customer Service and Technical Services directly as a crosscheck to the information obtained. The results of this study as a whole, the service customer complaints PT PLN (Persero) SemarangCentral Rayon can be quite good, if identified from four (4) dimensions of customer service complaints are used. Only on the dimension of empathy to angry customers, the speed in the face of the complaint, and easy for customers to contact the company who felt still need attention.